2010
DOI: 10.4103/0970-0218.66858
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and outcome measure of HbA1c testing in Asian Indian patients with type 2 diabetes from a tertiary care center

Abstract: Aim:HbA1c test is considered to be the reliable measure for evaluating long-term glycemic control in type 2 diabetes. The purpose of this study was to evaluate whether knowledge about HbA1c test is associated with a better glycemic control. Materials and Methods:We conducted a cross-sectional survey of 480 (M:F; 287:193) adults with type 2 diabetes attending a tertiary care center during a period of four months. Baseline demographic and clinical data of all the subjects was obtained. Subject’s knowledge about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…HCPs have a crucial role to play in discussing glycaemia results with their patients and formulating mutually agreed glycaemic targets. Kumpatla et al 30 showed that a knowledge of HbA1c and the target goal had a positive effect on maintaining better glycaemic control among people with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…HCPs have a crucial role to play in discussing glycaemia results with their patients and formulating mutually agreed glycaemic targets. Kumpatla et al 30 showed that a knowledge of HbA1c and the target goal had a positive effect on maintaining better glycaemic control among people with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The fundamentals of diabetes control largely depend upon drug therapy and lifestyle measures (increased physical activity and restriction of energy intake/diabetic diet) (6). Improved glycaemic control may reduce the development and progression of diabetic complications to some extent (7). Wealth of information is available on improving glycaemic control and decrease glycosylated haemoglobin (HbA1c) up to 2% through diet control (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated based on a study conducted by Manoharan D et al 8 which found that among the patients with diabetes since more than one year, 37.8% had HbA1c less than 7%. Using the formula sample size 𝑛 = ( -/ )…”
Section: Sample Size and Sampling Methodmentioning
confidence: 99%